The Influence of the Attention, Relevance, Confidence, Satisfaction (ARCS) Learning Model on Accounting Learning Outcomes for Class XII AK Students at SMK PAB 2 Helvetia in the 2018/2019 Academic Year - Elisabeth Sembiring (Outline Publisher, 2022)
The problem in this study is the low accounting learning outcomes of class XII students of AK SMK PAB 2 Helvetia. This study aims to find out the learning outcomes of accounting taught by the Attention, Relevance, Confidence, Satisfaction (ARCS) learning model are higher than the accounting learning outcomes taught using conventional methods in class XII AK SMK PAB 2 Helvetia in the 2018/2019 academic year. This research was conducted at SMK PAB 2 Helvetia which is located on Jl. Helvetia IV Market Veterans in the odd semester of the 2018/2019 Academic Year. The population in this study were all students of class XII AK SMK PAB 2 Helvetia. The sample used in this study was taken randomly (Simple Random Sampling), based on the lottery technique from class XII AK 1 as the experimental class and XII AK 2 as the control class. Then based on the Slovin formula, the number of samples was 48 students. The data analysis technique was carried out based on the different test of two averages. Based on the results of the analysis, it was found that the average pre-test and post-test of the experimental class were 56.46 and 83.96. While the average value of the pre-test and post-test of the control class was 59.38 and 73.33. Hypothesis testing shows that count = 4.72 > ttable = 1.677 in other words Ha is accepted and H0 is rejected. Thus, it can be concluded that the learning outcomes of accounting, on the subject of depreciation of fixed assets, which are taught with the Attention, Relevance, Confidence, Satisfaction (ARCS) learning model are higher than the accounting learning outcomes taught using conventional methods in class XII AK SMK PAB 2 Helvetia 2018/2019 Academic Year.